Pneumococcal serotype distribution in adults with invasive disease and in carrier children in Italy: Should we expect herd protection of adults through infants' vaccination?. Issue 2 (1st February 2016) - Azzari, Chiara; Cortimiglia, Martina; Nieddu, Francesco; Moriondo, Maria; Indolfi, Giuseppe; Mattei, Romano; Zuliani, Massimo; Adriani, Beatrice; Degl'Innocenti, Roberto; Consales, Guglielmo; Aquilini, Donatella; Bini, Giancarlo; et al.
ABSTRACT: The 7-valent pneumococcal conjugate vaccine (PCV7) produced a significant herd protection in unvaccinated adult population mostly because of pneumococcus carriage decrease in vaccinated children. It is not known if the 13-valent pneumococcal vaccine can give similar effect on adults. Aims of the work were to evaluate whether the 6 additional serotypes are present in nasopharynx of children and serotype distribution in invasive pneumococcal infections (IPD) in adults. Realtime-PCR was used to evaluate pneumococcal serotypes in adults with confirmed IPD and in nasopharyngeal swabs (NP) from 629 children not vaccinated or vaccinated with PCV7 and resident in the same geographical areas. Two hundred twenty-one patients (116 males, median 67.9 years) with IPD were studied (pneumonia n = 103, meningitis n = 61 sepsis n = 50, other n = 7). Two hundred twelve were serotyped. The most frequent serotypes were 3, (31/212; 14.6%), 19A, (19/212; 9.0%), 12 (17/212; 8.0%), 7F, (14/212; 6.6%). In NP of children, the frequency of those serotypes causing over 50% of IPD in adults was very low, ranging from 0.48% for serotype 7F to 7.9% for serotype 19A. On the other side serotype 5, very frequent in NP (18.7%) caused <1% IPD. In conclusion serotypes causing IPD in adults are very rarely found in children NP. We suggest that herd protection obtainable with the additional 6 serotypes included in PCV13 may be more limited than that demonstrated with PCV7 in the past. In order to reduce the burden of disease in adults, adults should be offered a specific vaccination program with highly immunogenic PCV.